PADDY PAST TRAP SYSTEM BASED ON LONG RANGE COMMUNICATION - Juanda, Juanda; Marpaung, Jannus; Putra, Leonardus Sandy Ade; Imansyah, Fitri; Yacoub, Redi Retiandi (Faculty of Engineering, Universitas Tanjungpura, 2023)
Indonesia is an agricultural country that produces rice plants. The decline in crop yields was caused by pests and had an impact on rice plants which experienced yellowing leaves, broken stems, until the rice fruit became empty. Test results data in the form of numbers in certain units will be presented in the form of tables and graphs. To find out the symptoms or behavior of the system at the time of testing, an analysis is carried out. The research was conducted for 5 nights starting at 18.00 until 06.00 WIB. The LoRa sender will send data when a pest lands on a 1000-1500 VDC wire net. In the research conducted, a total of 97 pests were found. The peak of pest attacks occurs at 19:00 to 20:00 WIB. Walang sangit attacks rice plants in all phases, so it is not surprising that this pest has the largest number, namely 87 pests. The rain that falls makes the lights dim thereby reducing the interest of the pests in the pest traps. Lamps with a wavelength of 500 nm can attract the attention of nocturnal pests that attack rice plants at night.